Two ways of conceiving time in sports [Dva způsoby pojímání času ve sportu] - Jim Parry; Irena Martínková (Palacky University, 2011)
BACKGROUND: This paper explores a foundational concept for our understanding of sport - the concept of time. OBJECTIVE: The objective of this paper is to explain two different concepts of time in sport. METHODS: Our methodology is philosophical, involving both conceptual and phenomenological analysis and the application of the outcomes to sports practice. RESULTS: First, two concepts of time and their role in sport are discussed - time as linear, measurable, homogeneous and objective; and time as discussed in the philosophy of existence, namely in the work of Martin Heidegger, in which he introduces the concept of "original temporality". Second, sports are classified into four different groups depending on the role of time in them, and basic characterisations of each are worked out. While within the first three groups the concept of objective time is salient, a suggestion is made regarding the potential of the fourth group, which includes high risk sports, for the realisation of original temporality. CONCLUSIONS: The two concepts of time presented in this paper explain the basis of sport and show its relationship to the human experiencing of sport activities. The text shows that the concept of objective time is necessary for the practice of some sports, whilst other sports use it rather in a secondary way, e. g. for the comparison of winners. Original temporality as a basis of human experiencing is present in all sports. While in most of them it is limited by objective time, in some sports (especially in high risk sports) the possibility of the realization of original temporality is opened. [VÝCHODISKA: Text se zabývá jedním ze základních pojmů ve sportu - pojmem času. CÍLE: Cílem textu je vysvětlit dvě různá pojetí času ve sportu. METODIKA: Naše metoda je filosofická a zahrnuje pojmovou a fenomenologickou analýzu a aplikaci výsledků do sportovní praxe. VÝSLEDKY: Nejprve jsou diskutovány dva pojmy času a jejich role ve sportu - pojetí času jakožto lineárního, měřitelného, homogenního a objektivního a čas v podání filosofie existence, zvláště v pojetí Martina Heideggera, který představuje pojem "původní časovost". Poté jsou sporty rozděleny do čtyř různých skupin v závislosti na roli, kterou v nich hraje čas, a jsou rozpracovány jejich základní charakteristiky. Zatímco v rámci prvních tří skupin se ukazuje důležitost objektivního času, čtvrtá skupina sportů, která zahrnuje vysoce rizikové sporty, poukazuje k možnosti realizace původní časovosti. ZÁVĚRY: V textu jsou představena dvě pojetí času, která vysvětlují základ sportu a která jsou vztažena k lidskému prožívání v rámci sportovních aktivit. V textu je ukázáno, že pojem objektivního času je nutný pro praktikování některých sportů, jiné sporty jej využívají spíše sekundárně, např. pro možnost porovnávání vítězů. Původní časovost se jakožto základ lidského prožívání ukazuje ve všech sportech. Zatímco v některých sportech je původní časovost omezována objektivním časem, v jiných (zvláště ve vysoce rizikových sportech) se naopak ukazuje možnost realizace původní časovosti.]